2019
DOI: 10.3390/rel10100589
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Innovation in Europe: Implications for Product Life-Cycle Management

Abstract: This paper analyzes the relationship between religion and innovation in Europe. To the best knowledge of the authors, no paper has been published about the association of religion with innovation and innovative products and services, at an individual level, for all the countries that belong to the European Union. This is the main goal of our paper. The results show that the orientation of innovativeness depends on religion. This study contains a segmentation of the main religions in Europe, taking into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Such composite indexes are unique but separate indicators used in previous literature (Sivak et al, 2011): Hilary and Hui (2009) used ARDA. The main purpose of using this variable is to evaluate the religiosity level in sample countries, which, according to the previous studies (Recio-Rom an et al, 2019;Gursoy et al, 2017;B enabou et al, 2015b), has an impact on corporate innovation.…”
Section: Methodology 41 Data Sourcesmentioning
confidence: 99%
“…Such composite indexes are unique but separate indicators used in previous literature (Sivak et al, 2011): Hilary and Hui (2009) used ARDA. The main purpose of using this variable is to evaluate the religiosity level in sample countries, which, according to the previous studies (Recio-Rom an et al, 2019;Gursoy et al, 2017;B enabou et al, 2015b), has an impact on corporate innovation.…”
Section: Methodology 41 Data Sourcesmentioning
confidence: 99%
“…The research at the intersection of religion and innovation has begun to flourish following the aforementioned studies (Huang et al, 2016;Assouad and Parboteeah, 2018;Recio-Román et al, 2019). However, no empirical study has considered the potential endogeneity of religion so far, despite reverse causality and identification problems have been recognized in the literature (Guiso et al, 2003).…”
Section: Religion Economic Outcomes and Innovationmentioning
confidence: 99%
“…To our knowledge, Benabou et al (2013) is the first empirical study at the intersection of religion and innovation. Following their contribution, the research in this field has begun to flourish (Perret, 2014;Chen et al, 2014;Benabou et al, 2015;Huang et al, 2016;Cinnirella and Streb, 2017;Assouad and Parboteeah, 2018;Recio-Román et al, 2019). Previous studies have consistently demonstrated a correlation between religion and innovation yet recognise that observed associations probably do not identify whether religion has a causal impact on innovation due to the potential endogeneity of religion.…”
Section: Introductionmentioning
confidence: 99%
“…'Academia is embedded in prestige economies' (Baker, 2019: 1) and I am now a doctoral graduate. Even as I was still wearing the cloak of stigma often bestowed on individuals who have withdrawn from the educational system, I was nonetheless validated and cited by some important figures in multiple fields of study, such as religious studies (Recio-Román et al 2019;Van Liere, 2020), family studies (Ribbens-McCarthy, Gillies and Hooper, 2019), organized crime (Hall et al 2020), counter-fraud studies (Button and Whittaker, 2020;Wang et al 2020), social psychology (Nartova-Bochaver et al 2018;Tsumura et al 2018) and legal studies Kirillova et al 2017;Orji, 2019). An author's career stage and popularity in the field can influence the citation rate of their publication outputs (Lazarus, 2020;Nightingale and Marshall, 2013).…”
Section: When Every Star Is Awaymentioning
confidence: 99%